Educational programs for rural communities - Joseph K. Rippetoe; Cecil James Killacky (Educational Considerations, 1977)
A voluntary association may be defined as "a group of persons relatively freely organized to pursue mutual and personal interests or to achieve common goals, usually non-profit in nature."